Tritium-Labeled Compounds II. General-Purpose Apparatus, and Procedures for the Preparation, Analysis, and Use of Tritium Oxide and Tritium-Labeled Lithium Borohydride - Isbell, Horace S. (J Res Natl Bur Stand A Phys Chem, 1959)
A general-purpose manifold is described, which is useful for numerous procedures involving tritium gas and tritium-labeled materials. Methods are given in detail for (a) converting tritium gas to tritium oxide, (b) preparing tritium-labeled lithium borohydride, and (c) conducting a variety of reactions in a closed system. Auxiliary equipment is shown, including water traps, reaction flasks, and apparatus for preparing solutions and making filtrations in closed systems. Methods are presented for assaying tritium-labeled water by (a) dissolving it in a phosphoric anhydride-sulfuric acid solution and counting in a windowless, gas-flow, proportional counter, or (b) converting it to hydrogen-t and assaying it in an ionization chamber. The use of tritium-labeled lithium borohydride is illustrated by the preparation of d-galactitol-1-t from d-galactose. Subsequent papers will describe the use of this apparatus in the synthesis of tritium-labeled carbohydrates. The detailed description of techniques and apparatus should be helpful to others who are interested in using tritium.